A Modification of the Frechet Distance for Nonnisomorphic Trees - Vodolazskiy, Ye.V. (Control systems & computers, 2021)
The paper presents a modification of the Frechet distance for nonisomorphic trees. While the classical Frechet distance between nonisomorphic trees is undefined, a new measure called similarity of a tree to a reference tree is given that is defined for a wider class of trees. A polynomial time algorithm is given for determining whether similarity of one tree to another is less than a given number.